KONSEP PENDIDIKAN KARAKTER K.H ABDURRAHMAN WAHID - Hidayat, Fariz N; Muslihah Difa Lailaturrahmah; Khanna Uly Rosyida (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to deeply analyze and describe the concept of character education initiated by Kiai Haji Abdurrahman Wahid (Gus Dur), who is a central figure in Indonesian Islamic and national discourse. The method employed by the author in compiling this article is Library Research, which involves collecting data sources from various literature related to the topic of discussion. Gus Dur's thinking on character education is rooted in universal Islamic values that are integrated with the social, cultural, political context, and principles of democracy. Gus Dur consistently rejected exclusive and fundamentalist approaches, instead promoting an open, tolerant, and inclusive attitude as the main foundation of education. For Gus Dur, education has a fundamental role as a source of human freedom and a means to achieve self-reliance and better quality of life. His philosophical foundation is strongly based on the principles of humanism and respect for human rights, linking these values to the basic principles of Islam (Al-Kulliyat al-Khams). He emphasized that Islamic education must liberate humanity from oppression and foster responsible freedom. Education, according to him, is an effort to humanize people (humanization) through the formation of character (akhlak), spirituality, and social awareness. The implementation of Gus Dur's ideas in the world of education centers on cultivating the value of tolerance as a primary characteristic, which respects religious plurality, culture, and worldviews. He also advocated for a humanistic and democratic education system, rejecting authoritarianism in the classroom, and encouraging students to think critically, creatively, and openly. Teachers are positioned as companions, not rulers. The core values of character education in Gus Dur's view include religiosity, honesty, tolerance, discipline, democracy, love of peace, social care, and responsibility. These values are realized in education that balances the cognitive, affective, and psychomotor domains. Specifically within the pesantren (Islamic boarding school) context, he emphasized three main values: viewing life as an act of worship, a love for religious knowledge, and sincerity (ikhlas) in work. ABSTRAKEskalasi intoleransi dan degradasi moral di era kontemporer menuntut reorientasi pendidikan karakter yang lebih substantif dan kontekstual. Namun, eksplorasi konseptual berbasis pemikiran tokoh bangsa, khususnya K.H. Abdurrahman Wahid (Gus Dur), masih minim dilakukan dalam diskursus pendidikan nasional. Penelitian ini bertujuan mengonstruksi konsep pendidikan karakter Gus Dur serta relevansinya sebagai landasan moral pendidikan modern. Metode: Studi ini menggunakan metode library research dengan pendekatan analisis deskriptif kualitatif. Data dikumpulkan dari literatur primer dan sekunder yang menelaah pemikiran Gus Dur terkait humanisme, keislaman, dan pendidikan. Hasil: Temuan menunjukkan bahwa konstruksi pendidikan karakter Gus Dur berakar pada integrasi nilai universal Islam, humanisme, dan demokrasi. Inti gagasannya adalah